The effectiveness of two counseling programs (acceptance and commitment, and Logo counseling) in reducing the existential vacuum and improving life skills among widows in Riyadh - Samiha Muqbil Abdullah Alharbi; Yahya Mubark Suleiman Khatatbeh (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
This study aimed to identify the effectiveness of two counseling programs (counseling by acceptance and commitment, and Logo counseling) in reducing the existential vacuum and improving the life management skills of widows. The study sample consisted of 27 widows; they were randomly divided into 3 groups of 9 for each group: (the counseling group with acceptance and commitment, the counseling group with meaning, the control group). The results of the study indicated that there were statistically significant differences between the average ranks of the counseling group with acceptance and commitment, the counseling group with meaning, and the control group; On the scale of the existential void in the dimensional measurement in favor of the two experimental groups, where it was in favor of the counseling group with acceptance and commitment in the total degree and subsequent feeling being connected, the differences between the two programs were equal in the other dimensions. There were statistically significant differences between the average ranks of the counseling group with acceptance and commitment, the counseling group with meaning, and the control group. On the scale of life management skills in the dimensional measurement in favor of the two experimental groups, it was in favor of the meaningful counseling group in the dimension of time management skills and subsequent effective communication skills, while the differences between the two programs were equal in the total score and the other dimensions. There were statistically significant differences between the average ranks of the counseling group with acceptance and commitment, the counseling group with meaning, and the control group. On the existential void scale in measuring follow-up in favor of the two experimental groups, no differences appeared between the two programs. Finally, there were statistically significant differences between the average ranks of the counseling group with acceptance and commitment, the counseling group with meaning, and the control group. On the life management skills scale in measuring follow-up in favor of the two experimental groups, there were no differences between the two programs.